Questioning Public Participation in Social Media Activities in Indonesia - Sokowati, Muria Endah (Komunikator, 2019)
The growth of using social media in Indonesia since 2009 has enabled the user to contribute in online discussion, share opinion and feeling, or circulate the digital creativities. Social media gives opportunities to its users to be the content providers. The number of users take part of the discussion in social media has brought Indonesia mentioned as the capital of social media world. This label attached to Indonesia since some big cities in Indonesia, such as Jakarta, Yogyakarta, and Bandung recorded as the cities whose residents become the most active social media users in the world. This phenomenon leads to the assumption that social media is success in creating public participation. But, is it true? Based on data from Association of Internet service provider (APJII), the Internet users dominated by people from middle class, urban, young and well-educated groups. Some blank spots in Indonesia, the high price of technology, the lack of quality in operating and using technology become the problems causing the difficulty in implementing public participation. This paper tried to explore the misleading of the assumption that social media activities in Indonesia have created public participation. It also analyzes on how digital divide becomes the barrier to gain the public participation.